A Shrinking Core Model Approach to Designing a Natural Gas Desulphurization Unit - Norain Binti Mohamad Adanan, Norain (Universiti Teknologi Petronas, 2011)
Sulfur compounds especially H2S should be safely removed from the natural gas. Known as one of the major environmental hazards, H2S is undesirable because of its toxicity in nature. The sulfur compounds can be poison to human health through several routes including by ingestion, intravenous and intraperitoneol. It can cause irritant to eyes, respiratory system and skin. In an industry, process for desulphurizing is required as traces of sulfur compounds can corrode equipments and poison other metal catalysts. Hence, desulphurization column is highly necessary to be used in industry to remove sulfur compounds to as low as 1 ppm. However, problems occur as there is insufficient of simple methodology in designing the desulphurization column systematically. Thus, aim of the project is to provide an efficient and simple methodology and framework in designing the desulphurization column by using shrinking core model approach. Noncatalytic gas solid reaction between ZnO which act as an adsorbent and H2S was studied. The results show that the kinetic behaviors of the reaction can be described by an improved shrinking core model. An analysis on H2S concentration, radius of adsorbent and temperature of reaction has been made to observe the effects of these factors on desulphurization and adsorption capacity. Application of the model is performed by using existing fertilizer data. It is found that the breakthrough or service time for a single pellet of ZnO adsorbent with a radius of 2mm at 673K and 43atm is 66.8 min. By using a simple and proper scale up technique, the desulphurization column has been designed. Reasonable dimensions of the desulphurization column show that the improved shrinking core model can be used for the industrial usage. Comparison of dimensions of the desulphurization column between results from improved shrinking core model and existent desulphurization column gave very low sums of squares error which is 0.0028. It is noted that the desulphurization column can be designed by taking a basis of a single pellet and scale it up to a column.